Technological Stratification of the Large Business Enterprises’ Development - AKHMETSHIN, Elvir M.; STEPANOVA, Diana I.; ANDRYUSHCHENKO, Iryna Ye.; HAJIYEV, Hafis A.; LIZINA, Olga M. (Journal of Advanced Research in Law and Economics, 2019)
Large business enterprises currently form the basis of both businesses in general and social development. The paper notes that the target existence of a large business enterprise is the ability to accumulate funds and create innovative products. It is noted that on the whole such elements are consolidated and gradually implemented in the social and economic environment of the state. The work uses econometric methods that allow fully revealing the reasons for differentiation of large business enterprises and determining the index parameters of the demand for development for the subsequent infrastructural transformation. It is pointed out that the effect of such activity is achieved not only as the profit received, but also in the overall perception of the commodity market. The novelty of the research is the indicators that the largest technological and structural companies that implement the majority of innovations at the core level of their system were analyzed and indices that evaluate in a comprehensive manner all possible types of innovations and the level of their implementation are provided. The direction of further research is the calculation of the possible institutional transformation of large business objects into state entities or objects with such characteristics.